الأبعاد الفنية في رواية" همس الهمس" لمحمد الكامل زيد - دغمان, علي; لعميري, هدى; خزان, هناء; قاسمي, سميرة (University of Eloued جامعة الوادي, 2024)
ندرس في هذا البحث الأبعاد الفنية في رواية "همس الهمس" لمحمد الكامل بن زيد من خلال الوقوف على أبعادٍ ثلاثة؛ وهي: - البُعد التخييلي من حيث إنّ أحداث الرواية تستند إلى حقائق موثّقة تُجسّدُ مرجعية لعالمٍ سرديّ فيه إنارة لقضيّة الرواية الكُبرى. - والبُعد التاريخيّ من حيث إنّه يرفُض الواقع الموثّق ويُعطي منْظورا جديدا للأحداث التاريخيّة، - والبُعد الأُسْطُوري من حيث إنّه يتأرجَح بين كَفّتيّ التخييل والتاريخ باعتبار مرجعيّته الواقعية الموثّقة التي تَخْفت مع اندِماجِها في أحداث الرواية. وكل ذلك يتم لأجل خدمة الحدث الأـكبر في الرواية؛ وهو إعادة تسليط الضوء على قضيّة التفجيرات النووية في صَحراء الجزائر التي تُصَادِف تاريخ 13 فيفري1960، وبالتالي إدانة أكبر جريمة نووية في العالم. In this work, we study the artistic dimensions in the novel "hams- al hams" "whisper's whisper" by Mohammed Al-Kamel Ben Zeid by examining three dimension, which are: - The imaginative dimension in that the events of the novel are based on reliable facts that embody a reference for a narrative word that illuminated the novels major issue. - The historical dimension in that it documented reality is rejected and given away a new perspective on historical events. - The mythical dimension in that it oscillates between the two sides of imagination and history, given its documented realistic reference, which disappears with its integration in to the events of the novel. All of this is done in order to serve the biggest event in the novel, which is to re-shed light on the issue of nuclear explosions in the Algerian desert which coincides with the date of February 13th,1960, thus condemining the largest nuclear crime in the world.
أدب حديث ومعاصر
Keywords: الرواية، الأبعاد الفنية، البعد التخييلي، البعد التاريخي، البعد الأسطوري، التفجيرات النووية.; The novel; the artistic dimensions; the imaginative dimension; the historical dimension; the mythical dimension; nuclear explosions.